Disaster Preparedness Impact In A Complex Ophthalmology Practice: A Review Of Patients Receiving Intravitreal Injections - El Hamichi S (Dove Medical Press, 2019)
Sophia El Hamichi, Aaron S Gold, Veronica Kon Graversen, Azeema Latiff, Timothy G Murray Murray Ocular Oncology and Retina (MOOR), Miami, FL, USACorrespondence: Sophia El HamichiMurray Ocular Oncology and Retina (MOOR), 6705 Red Road, Suite 412, Miami, FL 33143, USATel +12675519677Email sophiaelhamichi@gmail.comPurpose: A private tertiary care ophthalmology practice was analyzed to see how Hurricane Irma affected patient care.Methods: Eighty-two patients (96 eyes) that missed their scheduled appointments due to Hurricane Irma were reviewed. Patients were being treated with intravitreal injection therapy for diabetic retinopathy, radiation retinopathy, vein occlusions, choroidal neovascularization, or neovascular age-related macular degeneration. The authors assessed patients’ visual acuity and macular thickness changes before the hurricane and their initial visit after the storm. Emergency preparedness was also evaluated in this setting.Results: Patients on average were delayed 19.6 days. On average, best-corrected visual acuity was 20/97 (0.7 logMAR) before the hurricane and 20/82 (0.6 logMAR) after the storm. The average central macular thickness change was −1.30 μm. Intraocular pressure was not significantly affected and there were no ocular complications associated with the delay in therapy. A back-up electrical system was in place to maintain appropriate temperature for storage of medications and proper access to medical records.Conclusion: The authors believe that minimizing delay in treatment was the most important contributing factor to preventing worsening of ocular disease. Ophthalmology clinics should strive for appropriate treatment modality regarding injection intervals prior to a natural disaster and emergency planning with excellent patient communication both before and after natural disasters.Keywords: ophthalmology, intravitreal injections, hurricane, natural disaster, tertiary care